The Effects of Resistance Exercise on Blood Glucose Levels and Ankle-Brachial Index in Patients with Type 2 Diabetes Mellitus - Khotimah, Siti; Sari, Nova Nurwinda; Sari, Septi Kurnia (Genius Journal, 2025)
Introduction: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder marked by elevated blood glucose levels due to insulin resistance or impaired insulin secretion. The rising prevalence of T2DM in Indonesia, particularly in Bandar Lampung, highlights the need for effective interventions. While programs like Prolanis offer basic support, specific interventions to improve vascular health and prevent complications are still limited. Objective: This study aimed to assess the effect of resistance exercise on blood sugar levels, foot sensitivity, and ankle-brachial index (ABI) values in patients with T2DM at Kedaton Health Center, Bandar Lampung. Method: A quantitative quasi-experimental design with a one-group pretest-posttest model was used. Thirty-two individuals with T2DM were selected through purposive sampling. Participants underwent resistance exercise interventions involving repetitive limb movements. Blood sugar levels and ABI values were measured before and after the intervention. Results: The results demonstrated a significant decrease in blood sugar levels and a notable improvement in ABI values after the intervention, with both outcomes showing a p-value of 0.000. These findings indicate that resistance exercise can enhance glycemic control and peripheral vascular function. Conclusion: Resistance exercise significantly reduces blood sugar levels and improves ABI values in individuals with T2DM. This form of physical activity offers a promising non-pharmacological approach to managing diabetes and preventing complications. It is recommended that resistance exercise be integrated into routine diabetes care programs. Further research with varied methods and larger samples is encouraged to validate and expand these findings.